REVERSING AGING BY IMPROVING ENERGETICS, STRENGTH, COGNITION AND INFLAMMATION IN OLDER HUMANS: ROLE OF GLUTATHIONE. (16th November 2018) - Sekhar, R; Kumar, P; Minard, C; Liu, C
Abstract: Aging in older humans is associated with impaired mitochondrial fatty-acid oxidation (MFO), muscle weakness, cognitive decline and inflammation, but contributing mechanisms are not well understood and effective interventions are lacking. We proposed a unifying hypothesis that deficiency of the endogenous antioxidant protein Glutathione predisposes to all of these defects which are reversible on correcting Glutathione deficiency. To test our hypothesis, we conducted a 36-week open label clinical trial (NCT02348762) in 8 older humans (73.8 ± 1y) studied before and after 24-weeks of supplementation with N-acetylcysteine and Glycine (NAC-Gly, as Glutathione precursor amino-acids), and again 12-weeks after stopping supplements to determine washout changes. 8 young humans (25.8 ± 1y) served as controls, and were not supplemented. Study measures were intracellular Glutathione, fasted MFO (calorimetry), physical function (gait-speed, grip-strength, chair-rise and 6-minute walk tests), cognition (MoCA, Montreal Cognitive-Assessment; trail-making tests; verbal-fluency test; symbol-digital modalities test), plasma oxidative-stress (F2-isoprostanes), inflammation (Interleukein-6; Tumor Necrosis Factor alpha; C-reactive Protein) and body composition (DEXA-scan). Compared to young-controls, older humans had significantly (P<0.05 to P<0.01) impaired MFO, physical and cognitive decline, and higher inflammation and body fat. After 24-weeks of supplementation outcome measures improved significantly (P<0.05 to P<0.01), with complete normalization of fMFO (P<0.001), gait-speed (strength, P<0.001) and MoCA (cognition, P<0.01) to young controls. Accrued benefits declined on stopping supplementation. These novel discoveries provide a proof-of-concept for the exciting possibility that supplementing NAC-Gly in older humans could offer a novel nutritional approach to reverse age-related abnormalities in mitochondrial energetics, physical function, cognition, inflammation and body composition, and thereby 'reverse aging'.